Analisis Kinerja Pegawai Pada Perusahaan Pertambangan Minyak dan Gas Bumi Nasional (studi pada Kantor JOB Pertamina – Talisman Jambi Merang) - Bagus Ari Tio Ramadhan; Zainal Hidayat; Aloysius Rengga (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Increasing the quality of human resources is a reasonable process of change experienced by the middle of the nation growing. The attitude of the community began to grow a critical moment among others by presenting the demands of the employee's performance will be mainly on public organizations both STATE-OWNED ENTERPRISES or Government agencies. Both STATE-OWNED COMPANIES and Government agencies are already supposed to have employees with good performance. Pertamina is one of Indonesia's largest STATE-OWNED companies have, in fact, has a capacity of employees with a quality performance, but that there is still a lot of current related problems thus optimizing the performance of employees. But as the economic powerhouse of the nation of Pertamina which are State-owned enterprises in the fields of energy, oil and gas would largely determine the life of the people. Based on the above, the study will analyse the performance of the employees who performed on subsidiary Pertamina in Office JOB Pertamina-Talisman Jambi Merang and aware of the factors that hampered the optimization of the performance of the employees. This research uses the theory of employee performance measurement instrument on corporate indicator of where his judgement is the work achievement, skills, behavior and leadership. Data collection techniques used through observation, interview, documentation and library studies with informant in JOB Pertamina-Talisman Jambi Merang Office. The results showed the performance of employees in an Office JOB Pertamina-Talisman Jambi Merang yet arguably optimal. There are still some factors restricting in optimizing the conditions of performance of employees. These factors is factor of personnal, factor of team and factor of system. In overcoming barriers these there were some suggestions that can be done such as give a clear dissemination of any related work deadline and officials in the Division of tasks outside the Office, should have also held training in order to improve the quality of human resources, absent a more modern system is also not less important to enhance discipline employees, increased assertiveness in leadership style applied